Simbolisme Onak Duri dan Mahkota Duri dalam Kejadian 3:18 dan Matius 27:29: Implikasi untuk Rencana Keselamatan Manusia - Goni, Edwin Eldrich; Nainggolan, Bartolomeus Diaz (Institut Agama Kristen Negeri Palangka Raya, 2024)
This research aims to gain a comprehensive understanding of the symbolism of thistles and crown of thorns, the methodology used is qualitative, the author is actively involved in all stages of the research process, from defining the problem to reaching the findings. The research method used literature study with data processing procedures including interpretation and analysis of data to explain a more comprehensive significance of the Symbolism of Thistles and Crown of Thorns in Genesis 3:18 and Matthew 27:29: Implications for Human Salvation Plan. The results show that the symbolism of Jesus' crown of thorns reflects His faithfulness to God and His love for mankind, as well as His strength and dignity even in the midst of unjust suffering. The crown of thorns became one of the most powerful symbols in the Bible of Christ's sacrifice and suffering for the salvation of mankind.